The european digital fortress and large biometric EU IT systems - Završnik, Aleš (Dve domovini, 2019)
Today, at a time when we are witnessing the "multiplication of borders", borders are occupying new domains. The article focuses on the erection of digital borders by means of biometric technology, which is creating new knowledge through the compilation of large biometric databases in the EU. By "tattooing" borders onto immigrant bodies, disciplinary power is being superseded by the post-disciplinary power of "instant surveillance". The article continues by analysing re-bordering practices by means of seemingly apolitical information technology, and concludes by delving into the new harms caused by re-bordering, including violations of human rights and the emergence of multi-layered criminal law.
Keywords: biometric data; biometrični podatki; border criminology; človekove pravice; human rights; informacijska tehnologija; information technology; kriminologija meje; large IT database; podatkovne zbirke